Pyrocarbon Hemi-Shoulder Arthroplasty Provides Satisfactory Outcomes Following Prior Open Latarjet - Louis Lajoinie MD; Jérôme Garret MD; Floris van Rooij MSc; Mo Saffarini MEng; Arnaud Godenèche MD (Journal of Shoulder and Elbow Arthroplasty)
Purpose To assess the clinical and radiographic outcomes, at a minimum follow-up of 4 years, following HSA using pyrocarbon in patients that had prior open Latarjet. Methods The authors retrieved the records of 61 consecutive patients that underwent HSA with a pyrocarbon humeral head at 2 centers between December 2013 and October 2019. Eight patients (9 shoulders) had undergone previous Latarjet procedures without other surgical antecedents. Patients underwent radiological assessment, and clinical assessment including Constant score, Subjective Shoulder Value (SSV), and pain on VAS. Finally, range of motion was assessed, including active forward elevation and external rotation. Results The initial cohort of 9 shoulders, comprised 1 woman and 7 men (1 bilateral), aged 52.5 ± 5.2 at their index HSA, which was performed 27.7 ± 9.3 years following their prior Latarjet procedure. One shoulder required conversion to reverse shoulder arthroplasty, 3 years after HSA. The remaining 8 shoulders were assessed at 6.1 ± 1.6 years (range, 4-8) after the index HSA. Glenoid erosion only progressed in 1 shoulder from mild to moderate. The Constant score was 79.6 ± 12.7, pain on VAS was 1.0 ± 2.1, and SSV was 80.0 ± 25.6. The active forward elevation improved from 96°±41° to 151°±29°, and external rotation from 11°±17° to 32°±8°. Conclusion Patients that underwent HSA using pyrocarbon heads following prior Latarjet had satisfactory clinical scores, and glenoid erosion only progressed in 1 patient. Furthermore, only 1 patient required conversion to RSA. The clinical relevance is that HSA using pyrocarbon heads is a safe treatment and grants satisfactory clinical outcomes in patients with prior Latarjet. Level of Evidence Level III, retrospective comparative study